PHYTOCHEMICAL SCREENING, PHARMACOGNOSTICS CH- ARACTERIZATION, AND CHROMATOGRAPHIC ANALYSIS (TLC/HPTLC) OF STEVIA REBAUDIANA BERTONI LEAF EXTRACT - Jay Prakash Singh; Shikha Sharma (Current Research in Pharmaceutical Sciences, 2025)
The growing demand for natural sweeteners as alternatives to synthetic sugars has heightened interest in Stevia rebaudiana Bertoni, a perennial shrub native to South America, known for its high-intensity, non-caloric steviol glycosides. This study aimed to evaluate the pharmacognostic, phytochemical, and chromatographic properties of S. rebaudiana leaves to establish quality control parameters and validate its therapeutic potential. Fresh leaves were authenticated, shade-dried, and subjected to ethanolic extraction via cold maceration. Macroscopic and microscopic analyses revealed characteristic features such as lanceolate leaves with serrated margins, anisocytic stomata, and calcium oxalate crystals. Physicochemical evaluation showed acceptable moisture content (6.2%), total ash (9.4%), and extractive values (14.3% water-soluble). Phytochemical screening confirmed the presence of steviol glycosides, flavonoids, phenolics, and terpenoids, supporting its antioxidant and antidiabetic properties. Chromatographic profiling using TLC and HPTLC resolved key markers, with stevioside identified at Rf 0.67 (TLC) and 0.65 (HPTLC), providing a reliable fingerprint for standardization. The findings underscore S. rebaudiana’s potential as a natural sweetener and therapeutic agent, while establishing quality benchmarks for its use in nutraceutical and pharmaceutical applications. Further clinical studies are recommended to explore its efficacy and safety.